2017
DOI: 10.1139/gen-2016-0111
|View full text |Cite
|
Sign up to set email alerts
|

Transcript analysis in two alfalfa salt tolerance selected breeding populations relative to a non-tolerant population

Abstract: With the growing limitations on arable land, alfalfa (a widely cultivated, low-input forage) is now being selected to extend cultivation into saline lands for low-cost biofeedstock purposes. Here, minerals and transcriptome profiles were compared between two new salinity-tolerant North American alfalfa breeding populations and a more salinity-sensitive western Canadian alfalfa population grown under hydroponic saline conditions. All three populations accumulated two-fold higher sodium in roots than shoots as a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
17
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(17 citation statements)
references
References 33 publications
0
17
0
Order By: Relevance
“…Over-expression of NHX led to salinity tolerance in Arabidopsis (Apse et al, 1999). A recent transcriptome study revealed that alfalfa transporter genes HKT1 and anion exchanger maintained high transcript levels in salt tolerant alfalfa genotypes (Gruber et al, 2016). Na + influx can raise sodium concentration inside the cytosol activating K + efflux and disturbing K + /Na + ratio (Sun et al, 2009; Britto et al, 2010).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Over-expression of NHX led to salinity tolerance in Arabidopsis (Apse et al, 1999). A recent transcriptome study revealed that alfalfa transporter genes HKT1 and anion exchanger maintained high transcript levels in salt tolerant alfalfa genotypes (Gruber et al, 2016). Na + influx can raise sodium concentration inside the cytosol activating K + efflux and disturbing K + /Na + ratio (Sun et al, 2009; Britto et al, 2010).…”
Section: Discussionmentioning
confidence: 99%
“…Salinity induces expression of numerous genes to facilitate adaptive and defense responses in plants. The transcriptomes of two salt-tolerant alfalfa breeding populations were much more able to maintain their non-saline transcript levels and diversity under high saline conditions compared with a salt-sensitive population (Gruber et al, 2016). In terms of individual genes, salt-induced glycine rich plant proteins (GRPs) are characterized by their high content and repetitive sequences of glycine residues (Mangeon et al, 2010).…”
Section: Introductionmentioning
confidence: 98%
“…Several transcriptome-based and proteome studies have been conducted to understand salinity stress in alfalfa [49,54,66,[81][82][83][84][85][86][87]. After a three-day salt treatment, a proteomic study on the roots of two-week-old seedlings found 83 differentially expressed proteins in alfalfa cultivars with contrasting tolerances to salinity (Table 1) [81].…”
Section: Proteome and Transcriptomic Analysesmentioning
confidence: 99%
“…Transcriptomic approaches have been employed for alfalfa to understand the gene expression associated with salt stress (Table 1) [49,66,[83][84][85]87]. Eighty-two unique transcripts were found from the salt-stressed seedlings of alfalfa by sampling at different time intervals from 10 min to 24 h, including 24% that were proteins related to plant metabolism and 9% that were related to abiotic stress [87].…”
Section: Proteome and Transcriptomic Analysesmentioning
confidence: 99%
“…A recent surge in transcriptomic and metabolomic studies of Medicago spp. following challenge with abiotic stresses (Gruber et al, ; Miao et al, ; Postnikova, Shao, & Nemchinov, ; Zhang et al, ) will almost certainly aid in the further characterization of these molecular pathways and improve the ease with which alfalfa varieties with enhanced stress tolerance can be bred in the future. In addition, numerous preliminary studies using biotechnological approaches have shown great promise in terms of their potential for improving abiotic stress tolerance in model plant species using various strategies, such as the modulation of genes encoding signaling‐related kinases, structural or protective proteins, antioxidants or enzymes involved in the production of reactive oxygen species (ROS)‐scavenging or osmoprotectant molecules, transcription factors, and miRNAs; a growing number of which are now being found to extend to forage species such as alfalfa.…”
Section: Introductionmentioning
confidence: 99%